Epistemological Dimensions in Islamic Educational Philosophy: A Critical Analysis - Asyibli, Basri; Ibtihal, Aqila Azharrani; Fauzan, Mochamad Fikri; Fauzi, Anis; Hidayat, Wahyu (Journal of Islamic Education Research, 2025)
Epistemology, the philosophical study of knowledge, underpins how knowledge is acquired, validated, and applied. This research explores Islamic epistemology, which integrates divine revelation, reason, and experience as complementary sources of knowledge. By analyzing epistemological approaches such as empiricism, rationalism, and intuitionism, the study highlights their influence on Islamic educational principles and methodologies. Islamic education uniquely balances spiritual and intellectual pursuits, integrating scientific inquiry with religious values. The study discusses how these concepts shape curriculum design, teaching strategies, and learners' intellectual and moral development. Using library research, data from books, scholarly articles, and digital platforms provide a comprehensive understanding of epistemology’s role in Islamic education. The findings reveal that epistemology in Islamic education bridges traditional and modern knowledge frameworks, fostering holistic development. This understanding helps educators and learners create an inclusive learning process that harmonizes empirical and rational knowledge with spiritual insight.